Теоретико-прикладні аспекти бюджетування зовнішньоекономічної діяльності підприємств в умовах європейської інтеграції України - Кузьмін, О. Є.; Мельник, О. Г.; Адамів, М. Є. (Видавництво Львівської політехніки, 2015)
Обґрунтовано актуальність бюджетування зовнішньоекономічної діяльності для вітчизняних підприємств в умовах європейської інтеграції України. Розкрито актуальні зміни у податковому і бухгалтерському підходах до визнання витрат та обліку амортизації суб’єктів зовнішньоекономічної діяльності. Висвітлено ключові особливості бюджетного відшкодування податку на додану вартість для експортноорієнтованих підприємств. Викладено сучасні засади здійснення розрахунків іноземною валютою у зовнішньоекономічній діяльності суб’єктів господарювання. The actuality of research is caused by the necessity of implementation and realization of budgeting of foreign economic activity at the domestic enterprises in conditions of Ukraine’s European integration. It is proved that during the revitalization of European integration reforms in Ukraine foreign economic activity is one of the priority operation for local businesses that in conditions of its effective realization will enable enterprises to increase the effectiveness of their activities, ensure the rapid progressive development, consolidate the positions at European markets, create a positive image of the reliable partner, attract the new sources for financing of perspective projects and so on. Simultaneously, it is determined that at the present stage of the tough competition at international markets the requirements for subjects of foreign economic activity in the context of providing the high level of their competitiveness are largely growing. It is established that under the current socio-economic crisis in the country, that destabilized the financial positions of domestic enterprises, a constructive solution of the problem of low level of financial effectiveness, solvency, investment attractiveness and competitiveness of business entities is the implementation of progressive management technologies, including the budgeting of foreign economic activity. Budgeting of foreign economic activity of enterprises is aimed at the formation of a reasonable information basis about the financial sphere of the enterprise, increasing of its profitability, cash flow optimization within foreign economic activity, mutual coordination of financial relations with foreign partners. It is grounded that nowadays the reformations to the principles of national legal and regulatory basis towards its harmonization with international standards, which determine some features of the formation of basic budgets of enterprises in the conditions of foreign economic activity, are increasingly taking place. Based on the results of the research of latest trends of changes in the regulatory provision of foreign economic activity of enterprises it have been found the significant limitations of content and functional filling of tax approach to the recognition of costs and accounting of depreciation in favor of accounting approach, which actually occupies a key place in costs and depreciation areas. In addition, it is defined the key features of VAT refund for export-oriented enterprises, which are based on the simplified list of criteria for claiming such refund and, as well as provide an opportunity for business entities to obtain the compensation in the period in which it emerged. It is also established that nowadays intensive changes are appearing in the sphere of regulation of payments in foreign currency during the foreign economic relations. They are mainly related to the terms of enrollment of proceeds in foreign currency to the accounts of enterprises and the amount of mandatory sale of obtained revenues at the interbank foreign exchange market of Ukraine. It is proved that significant improvements in the principles of legal and regulatory basis in the context of its harmonization with international standards, which define the features of budgeting of foreign economic activity at enterprises, did not take place. It is requires the activation of further careful work in this direction of the higher and local authorities, as well as the managers and specialists of business structures and specialized organizations.
Theoretical and applied aspects of budgeting of foreign economic activity of enterprises in conditions of Ukraine’s European integration
Keywords: бюджетування; зовнішньоекономічна діяльність; нормативно-правова база; витрати; амортизація; відшкодування ПДВ; розрахунки; Європейська інтеграція; budgeting; foreign economic activity; legal and regulatory basis; costs; depreciation; VAT refund; payments; European integration